Detailed Pharmacognostical and Phyto Chemical Investigation of Aragwadha Phalamajja Cassia fistula L - Kumar, Vikram (International Journal of Pharmaceutical & Biological Archive, 2012)
Detailed Pharmacognostical and Phyto Chemical Investigation of Aragwadha Phalamajja Cassia fistula L